Using the Five Domains Model to Assess the Adverse Impacts of Husbandry, Veterinary, and Equitation Interventions on Horse Welfare - McGreevy, Paul (Animals (Basel), 2018)
SIMPLE SUMMARY: Using an adaptation of the domain-based welfare assessment model, a panel of horse welfare professionals (with professional expertise in psychology, equitation science, veterinary science, education, welfare, equestrian coaching, advocacy, and community engagement) assessed the perceived harms, if any, resulting from 116 interventions that are commonly applied to horses. Scores for Domain 5 (the integrated mental impact) gathered after extensive discussion during a four-day workshop aligned well with overall impact scores assigned by the same panellists individually before the workshop, although some rankings changed after workshop participation. Domain 4 (Behaviour) had the strongest association with Domain 5, whilst Domain 1 (Nutrition) had the weakest association with Domain 5, implying that the panellists considered commonly applied nutritional interventions to have less of a bearing on subjective mental state than commonly applied behavioural restrictions. The workshop defined each intervention, and stated assumptions around each, resulting in a set of exemplar procedures that could be used in future equine welfare assessments. ABSTRACT: The aim of this study was to conduct a series of paper-based exercises in order to assess the negative (adverse) welfare impacts, if any, of common interventions on domestic horses across a broad range of different contexts of equine care and training. An international panel (with professional expertise in psychology, equitation science, veterinary science, education, welfare, equestrian coaching, advocacy, and community engagement; n = 16) met over a four-day period to define and assess these interventions, using an adaptation of the domain-based assessment model. The interventions were considered within 14 contexts: C1 Weaning; C2 Diet; C3 Housing; C4 Foundation training; C5 Ill-health and veterinary interventions (chiefly medical); C6 Ill-health and veterinary interventions (chiefly surgical); C7 Elective procedures; C8 Care procedures; C9 Restraint for management procedures; C10 Road transport; C11 Activity—competition; C12 Activity—work; C13 Activity—breeding females; and C14 Activity—breeding males. Scores on a 1–10 scale for Domain 5 (the mental domain) gathered during the workshop were compared with overall impact scores on a 1–10 scale assigned by the same panellists individually before the workshop. The most severe (median and interquartile range, IQR) impacts within each context were identified during the workshop as: C1 abrupt, individual weaning (10 IQR 1); C2 feeding 100% low-energy concentrate (8 IQR 2.5); C3 indoor tie stalls with no social contact (9 IQR 1.5); C4 both (i) dropping horse with ropes (9 IQR 0.5) and forced flexion (9 IQR 0.5); C5 long-term curative medical treatments (8 IQR 3); C6 major deep intracavity surgery (8.5 IQR 1); C7 castration without veterinary supervision (10 IQR 1); C8 both (i) tongue ties (8 IQR 2.5) and (ii) restrictive nosebands (8 IQR 2.5); C9 ear twitch (8 IQR 1); C10 both (i) individual transport (7.00 IQR 1.5) and group transport with unfamiliar companions (7 IQR 1.5); C11 both (i) jumps racing (8 IQR 2.5) and Western performance (8 IQR 1.5); C12 carriage and haulage work (6 IQR 1.5); C13 wet nurse during transition between foals (7.5 IQR 3.75); and C14 teaser horse (7 IQR 8). Associations between pre-workshop and workshop scores were high, but some rankings changed after workshop participation, particularly relating to breeding practices. Domain 1 had the weakest association with Domain 5. The current article discusses the use of the domain-based model in equine welfare assessment, and offers a series of assumptions within each context that future users of the same approach may make when assessing animal welfare under the categories reported here. It also discusses some limitations in the framework that was used to apply the model.